Reduced Virulence of a Bordetella bronchiseptica Siderophore Mutant in Neonatal Swine - Register, Karen B. (American Society for Microbiology, 2001)
One means by which Bordetella bronchiseptica scavenges iron is through production of the siderophore alcaligin. A nonrevertible alcaligin mutant derived from the virulent strain 4609, designated DBB25, was constructed by insertion of a kanamycin resistance gene into alcA, one of the genes essential for alcaligin biosynthesis. The virulence of the alcA mutant in colostrum-deprived, caesarean-delivered piglets was compared with that of the parent strain in two experiments. At 1 week of age, piglets were inoculated with phosphate-buffered saline, 4609, or DBB25. Two piglets in each group were euthanatized on day 10 postinfection. The remainder were euthanatized at 21 days postinfection. Clinical signs, including fever, coughing, and sneezing, were present in both groups. Nasal washes performed 7, 14, and 21 days postinoculation demonstrated that strain DBB25 colonized the nasal cavity but did so at levels that were significantly less than those achieved by strain 4609. Analysis of colonization based on the number of CFU per gram of tissue recovered from the turbinate, trachea, and lung also demonstrated significant differences between DBB25 and 4609, at both day 10 and day 21 postinfection. Mild to moderate turbinate atrophy was apparent in pigs inoculated with strain 4609, while turbinates of those infected with strain DBB25 developed no or mild atrophy. We conclude from these results that siderophore production by B. bronchiseptica is not essential for colonization of swine but is required for maximal virulence. B. bronchiseptica mutants with nonrevertible defects in genes required for alcaligin synthesis may be candidates for evaluation as attenuated, live vaccine strains in conventionally reared pigs.